2021
DOI: 10.33536/jcpe.v6i1.593
|View full text |Cite
|
Sign up to set email alerts
|

Studi Komparasi Penggunaan TiO2 Anatase dan P25 sebagai Anoda pada Sel Surya Tersensitasi Bixin

Abstract: Penelitian ini dilakukan untuk menentukan kinerja sel surya yang menggunakan TiO2anatase dan TiO2-P25 sebagai anoda. Bixin digunakan sebagai sensitizer. Bixin diekstraksi dan diisolasi dari biji kesumba. Bixin dianalisis menggunakan spektrofotometer UV-Vis dan FTIR. Hasil analisis menggunakan spektrofotometer UV-Vis menunjukkan adanya 3 puncak karakteristik bixin pada 488, 459, 430 nm. Spektra FTIR bixin ditandai dengan adanya serapan pada bilangan gelombang 3183 cm -1 mengindikasikan vibrasi renggang -OH yang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Park [ 21 ] reported that anatase TiO 2 has a higher incident photon to current conversion efficiency (IPCE) value than rutile TiO 2 . Our previous research reported the adsorption of bixin as a sensitizer on the TiO 2 anatase surface followed the model of Langmuir (chemistry interaction), and the performance test of DSSC showed higher energy conversion efficiency than commercial TiO 2 P-25 [ 19 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Park [ 21 ] reported that anatase TiO 2 has a higher incident photon to current conversion efficiency (IPCE) value than rutile TiO 2 . Our previous research reported the adsorption of bixin as a sensitizer on the TiO 2 anatase surface followed the model of Langmuir (chemistry interaction), and the performance test of DSSC showed higher energy conversion efficiency than commercial TiO 2 P-25 [ 19 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…DSSC work analysis was carried out using an Agilent 34401A 6.5 digits multimeter by varying the intensity of the light given to the DSSC device. The intensity variations were 0, 5,6,7,8,9,10,20,30,40,50,60,70,80,90, and 100 mW cm -2 . The solar cells with the highest efficiency were chosen to irradiate periodically for several days until the solar cells died to measure reusability.…”
Section: Dssc Performance Analysismentioning
confidence: 97%
“…The peak that appears at a wavelength of 488 nm and 459 nm shows the existence of electron transitions from π to π* resulting from conjugated bonds C=C. While the peak at a wavelength of 434 nm appears because of the electron transition from n to π * produced by carbonyl group C=O [7,14,20].…”
Section: Bixin Extraction and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation